Developing Courses in Occupational Safety & Health and Corporate Social Responsibility: A Faculty Handbook - Puplampu, B. B.; Ofori, D. F.; Amponsah-Tawiah, K.; Dartey-Baah, K. (Cranfield Press: Bedfordshire, UK, 2013)
This is a handbook or resource book on mounting and delivering degree and post graduate courses in occupational health as well as corporate social responsibility in higher education programmes in business and/or social/environmental science programme in Africa.
Book
Keywords: Occupational Safety; Health; Corporate Social Responsibility